Computational modelling of the cyclic behaviour of short rubberized concrete-filled steel tubes. (1st December 2021) - Duarte, A.P.C.; Silvestre, N.; de Brito, J.; Júlio, E.
Graphical abstract: Highlights: Modeling of rubberized concrete-filled steel tubular columns under cyclic bending. Dynamic explicit analyses with kinetic energy control of short columns using ABAQUS. Influence of rubberized concrete (RuC) on columns' energy dissipation capacity (ΔE) Lower brittleness of RuC is offset by its lower strength, reducing (ΔE) of columns. RuC with increased strength is shown to potentially increase ΔE of columns. Abstract: In this paper, the mechanical behaviour of short rubberized concrete-filled steel tubular (RuCFST) columns with square cross-section under combined cyclic bending and (monotonic) compression is studied numerically. For this purpose, dynamic explicit analyses with kinetic energy control (for the quasi-static behavior to be obtained) using the commercial finite element modelling package ABAQUS were performed. Firstly, a brief introduction and literature review on the topic is made. Then, the numerical models are described in detail with emphasis on the modelling of the materials (natural aggregate concrete (NAC), rubberized concrete (RuC) and steel) under cyclic loading. An in-depth presentation of the numerical results is made afterwards. It includes firstly a verification of the models by comparison of the numerical results with their experimental counterparts, the latter previously obtained by the authors. Secondly, a numerical study on the effectiveness of RuC on the energy dissipation capacity of CFST columns under lateral cyclic loading is performed. It is concluded that the models yield similar results regarding stiffness, maximum loads, load–displacement curves and failure modes as those obtained experimentally, with RuC leading to a moderate reduction (of up to 2%) of the strength of the columns. Regarding the energy dissipation capacity of the columns, it is concluded that RuC generally leads to a reduction of this property (of circa 2.5% per each 5% of rubber aggregates replacement). The lower strength and stiffness of the RuC mixes designed for this study compared to NAC are found to generally offset the benefit of their lower brittleness in increasing the energy dissipation capacity of the columns.